Analysis of a gain tuning PID controller for pressure control in UCP plant - Abdullah, Nor Arymaswati; Che Soh, Azura; Abdul Rahman, Ribhan Zafira; Mohd Noor, Samsul Bahari (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents a pressure control in UCP plant system by tuning PID gain approach to obtain the desired signal response. The identification of input output of the pressure control was done in MATLAB and Lab view for PID controller process as well as PID gain. The simulation results shows there are improvement of signal under certain gain.